Konduktivitas Hidraulik Tanah Sebagai Indikator Pengelolaann Irigasi Dilahan Kering - Julvan Ndruru; Lola Sri Wahyuni Halawa; Dilva Dwi Wulan Halawa (CV. SINAR HOWUHOWU, 2025)
This study aims to explore the relationship between soil hydraulic conductivity and irrigation management in dryland areas. Soil hydraulic conductivity, which is a measure of the soil’s ability to transmit water, was measured at several locations with varying soil types. The results showed that sandy soils have higher hydraulic conductivity (an average of 1.2 cm/hour) compared to clay soils (0.15 cm/hour). In addition, a survey of 100 farmers indicated that more efficient irrigation practices were applied by those who understood their soil characteristics. Regression analysis showed that 67% of the variation in irrigation management efficiency can be explained by soil hydraulic conductivity. These findings highlight the importance of understanding hydraulic conductivity to improve irrigation management practices and agricultural productivity in dryland areas.